A review on liquid air energy storage: History, state of the art and recent developments. (March 2021) - Borri, Emiliano; Tafone, Alessio; Romagnoli, Alessandro; Comodi, Gabriele
Abstract: Liquid air energy storage (LAES) represents one of the main alternatives to large-scale electrical energy storage solutions from medium to long-term period such as compressed air and pumped hydro energy storage. Indeed, characterized by one of the highest volumetric energy density (≈200 kWh/m 3 ), LAES can overcome the geographical constraints from which the actual mature large-scale electrical energy storage technologies suffer from. LAES is based on the concept that air can be liquefied, stored, and used at a later time to produce electricity. Although the liquefaction of air has been studied for over a century, the first concept of using cryogenics as energy storage was proposed for the first time in 1977 and rediscovered only in recent times. Indeed, the need for alternative energy vectors in the energy system attracted many researchers to discover the potential of the use of cryogenic media. This has brought the realization of a first LAES pilot plant and a growing number of studies regarding LAES systems. The main drawback of this technology is the low round-trip efficiency that can be estimated around 50–60% for large-scale systems. However, due to its thermo-mechanical nature, LAES is a versatile energy storage concept that can be easily integrated with other thermal energy systems or energy sources in a wide range of applications. Most of the literature published is based on thermodynamic and economic analysis focusing on different LAES configurations. This paper provides a collection of the papers published on LAES and it classifies the various studies conducted in different categories. Future perspectives show that hybrid LAES solutions with efficient design of the waste energy recovery sections are the most promising configuration to enhance the techno-economic performance of the stand-alone system. Highlights: The state of the art of LAES is described. A detailed review of the studies published is reported. Future prospective can aim to develop LAES hybrid solutions with an efficient thermal energy recovery system.